(untitled) (Bangkok, Thailand, 2005)
The book reviews social movements and sugests ways for change in the future direction of forest management that will depend on opening up of new social spaces for wider debates and negotiations,....
Keywords: Forest management,Forest management,Logging,Quản lý rừng; Political aspects; Thailand.,Thailand,Thailand,Thái Lan